Inhibition of γ‐secretases alters both proliferation and differentiation of mesenchymal stem cells - Sonja Vujović; Stephen Henderson; Adrienne M. Flanagan; Mark O. Clements (2007)
Abstract. Introduction : Human mesenchymal stem cell (hMSC) proliferation and development is regulated by many signalling pathways. γ‐Secretases play an important role in Notch signalling as well as other processes that are involved in developmental decisions, but their role in hMSC proliferation and cell fate decisions has not been explored. Objective : To investigate the role of γ‐secretases in hMSC proliferation and differentiation. Materials and methods : Using the γ‐secretase inhibitor N‐[N‐(3,5‐Difluorophenacetyl‐L‐alanyl]‐S‐phenylglycine t‐butyl ester (DAPT), we investigated their role in hMSC growth and differentiation to chondrogenic, osteogenic and adipogenic fates. Results : We found that inhibiting γ‐secretases reduced the rate of hMSC proliferation, and altered hMSC differentiation in vitro . Addition of DAPT had an inhibitory effect on chondrogenesis resulting in impaired cartilage matrix production and altered chondrocyte morphology. DAPT treated chrodrocytic pellets had reduced levels of Hes1 and Hey1 suggesting that these effects are mediated via Notch signalling. Addition of the DAPT inhibitor to osteogenic cultures did not alter the appearance of bone markers, however, adipogenesis occurred in these cultures in a DAPT concentration‐dependent manner. DAPT did not enhance adipogenesis in the presence of a potent adipogenic cocktail, but had an adipogenic effect when combined with dexamethasone only. Conclusion : We conclude that γ‐secretases play an important role in both hMSC proliferation and differentiation.